IMPLEMENTASI PERATURAN DAERAH NOMOR 5 TAHUN 2013 TENTANG PENGELOLAAN SAMPAH DI KECAMATAN BARONG TONGKOK KABUPATEN KUTAI BARAT - Dominikus Baping; Dan Buntu Paranoan; Adam Idris (Jurnal Administrative Reform, 2017)
This research aims to describe, analyze and interpret the implementation of waste management In the District of Barong Tongkok, West Kuta. This study uses a qualitative approach with interview, observation and documentation and then analyzed using an interactive analysis model through a data reduction stage.